Effect of zinc nanoaquacitrate on the biochemical and productive parameters of the organism of rabbits - BoikoО. V.; HoncharО. F.; Lesyk, Y. V.; KovalchukІ. І.; Gutyj, B. V. (Regulatory Mechanisms in Biosystems, 2020)
Zinc is an essential microelement for the organism of animals, and its deficiency reduces the synthesis and degradation of proteins, lipids, carbohydrates and nucleic acids, and also decreases the metabolism of vital microelements. The objective of the study was determining the effect of various amounts of zinc nanoaquacitrate on the biochemical parameters of blood and productivity of the organism of rabbits after weaning on 50th to 86th days of life. Compared with the control group, intake of zinc nanoaquacitrate by the animals of the experimental groups exhibited dose-dependent effect on separate biochemical parameters which characterize the processes of lipid and mineral metabolisms, which manifested in the increase in their content in the blood on the 12th, 24th and 36th days of the experiment. Watering rabbits with zinc citrate in the dose of Zn 0.25 mg/kg after weaning determined its physiological effect on the biochemical parameters of their organism, expressed in the most statistically reliable changes compared with other tested amounts, particularly a higher level of the total protein, increase in the activities of glutathione reductase, alanine aminotransferase, catalase and alkaline phosphatase and decrease in the levels of cholesterol, lipid hydroperoxides, compared with the control, which may indicate the positive effect of the applied additives on certain biochemical parameters of the rabbits’ organism. Additional use of zinc citrate in the dose of 0.50 mg/kg of body weight was manifested in their blood by significant increase in the activities of catalase and glutathione reductase, lower level of lipid hydroperoxides and increase in the organism’s growth parameter by 3.1% in the final period of the study. Watering zinc citrate in the amount of 0.75 mg/kg of body weight provoked probable decrease in the level of cholesterol and triacylglycerols and increases in catalase and glutathione reductase, increase in activity of alanine aminotrasferase and decrease in lipid hydroperoxides, which determined the stimulating effect on the growth of the organism with 8.4% higher total gain of body weight after 36 days of the experiment. From a general perspective, the research indicates that intake of lowest amount of zinc citrate was characterized by the greatest effect on the biochemical blood parameters, whereas the use of greater amounts of organic compound of zinc showed positive effect on the processes of growth and development of the organism of rabbits after weaning. Of practical importance is the study of the effect of watering zinc nanoaquacitrate in the physiologically substantiated amounts on biochemical blood parameters and growth and survivability of the offspring and organism of the mother rabbit in the period of lactation.